Concurrency, Compositionality, and Correctness Essays in Honor of Willem-Paul de Roever - Dams, Dennis.; Hannemann, Ulrich.; Steffen, Martin. (Lecture Notes in Computer Science, 2010)
This Festschrift volume, published in honor of Willem-Paul de Roever, contains 19 detailed papers written by the friends and colleagues of the honoree, all eminent scientists in their own right. These are preceded by a detailed bibliography and rounded off, at the end of the book, with a gallery of photographs. The theme under which the papers have been collected is Concurrency, Compositionality, and Correctness, reflecting the focus of Willem-Paul de Roever's research career. Topics addressed include model checking, computer science and state machines, ontology and mereology of domains, game theory, compiler correctness, fair scheduling and encryption algorithms.